Habitat-driven variation in amino and fatty acid profiles of Rabbitfish from the Makassar Strait and Gulf of Bone, Sulawesi, Indonesia - IRMAN HALID; ARHAM RUSLI; PATAHIRUDDIN PATAHIRUDDIN; SISWATI SISWATI; MARHAYANA SYARIFUDDIN; WITNO WITNO; RIHADATUL AISYA AR RAZAK; IKBAL SYUKRONI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Halid I, Rusli A, Patahiruddin, Siswati, Syarifuddin M, Witno, Ar Razak RA, Syukroni I. 2025. Habitat-driven variation in amino and fatty acid profiles of Rabbitfish from the Makassar Strait and Gulf of Bone, Sulawesi, Indonesia. Biodiversitas 26: 4865-4873. This study aimed to determine the amino and fatty acid profiles of Rabbitfish (Siganus spp.) inhabiting different marine environments, specifically the Makassar Strait and the Gulf of Bone, Indonesia. Samples were collected from four locations: Balang Lompo Island, Panikiang Island, Karang-Karangan, and Batu Lotong waters. Freshly caught specimens were transported to the laboratory in ice-cooled containers to maintain sample integrity before preparation and biochemical analysis. To assess the effect of habitat, the amino acid and fatty acid compositions of rabbitfish muscle tissues were quantified, and the data were statistically analyzed using One-Way ANOVA. The results revealed significant habitat-driven variation, with rabbitfish collected from Panikiang Island exhibiting the most complete and diverse amino acid profile. Both essential and non-essential amino acids showed significant differences compared to the other three sites, except for glycine and cysteine, which remained relatively consistent. Similarly, the fatty acid profiles of Panikiang Island samples were more comprehensive, with higher concentrations and diversity than those of fish from Balang Lompo, Karang-Karangan, and Batu Lotong. These findings demonstrate that habitat characteristics play an important role in shaping the biochemical composition of rabbitfish, providing valuable insights into ecological adaptation, nutritional quality, and potential implications for fisheries management and aquaculture development.